Phytochemical Composition and Chronic Hypoglycemic Effect of Bromelia karatas on STZ-NA-Induced Diabetic Rats. (25th February 2019) - Escandón-Rivera, Sonia M.; Andrade-Cetto, Adolfo; Sánchez-Villaseñor, Gabriela
Abstract : Oral administration of an aqueous extract of the aerial parts of Bromelia karatas to STZ-NA rats showed a significant hypoglycemic effect in a chronic trial lasting 42 days. Chromatographic profiles of the active extract (WE) and an organic extract (OE) of B. karatas were obtained by high-performance liquid chromatography (HPLC) and used to identify their major components. Isolation and identification of the compounds present in the extracts were accomplished by means of various conventional chromatographic and spectroscopic techniques. This process led to the identification of β -sitosterol-3-O- β -D-glucopyranoside (1 ) and ρ -coumaric acid (3 ) as the major compounds present in the extracts. During the isolation of1 and3, seven additional metabolites not previously reported for the plant were obtained, namely, cirsiliol 4′-O- β -D-glucopyranoside (2 ), stigmasterol (4 ), β -sitosterol (5 ), 1-O-feruloyl-3-O- ρ -coumaroylglycerol (6 ), β -D-(1-O-acetyl-3, 6-O-trans-diferuloyl) fructofuranosyl- α -D-2′, 4′, 6′-O-triacetylglucopyranoside (7 ), 1-O-p-coumaroyl-3-O-caffeoylglycerol (8 ), and 2-propyl- β -glucopyranoside (9 ).